Deli Husada Sosialisasi Program K3 Di Rumah Sakit Grandmed Lubuk Pakam - Hana Isal Salina; Hazimah Fithryyah Mardatillah Mahziah Ahmad (LLPM Universitas Deli Sumatera, 2024)
The implementation of Occupational Safety and Health Management System (SMK3) in Grandmed Hospital Lubuk Pakam is important to protect workers and improve hospital performance. This study uses mixed methods with exploratory design to analyze the implementation of SMK3 in Grandmed Hospital Lubuk Pakam. The results of the study indicate that Grandmed Hospital Lubuk Pakam has implemented several SMK3 elements such as OHS policies, planning, and monitoring, but several aspects, such as continuous technical training and waste management, need to be improved. This study provides recommendations to strengthen the implementation of SMK3 through the formation of a special team and increasing management commitment